2016
DOI: 10.1097/md.0000000000003630
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the Older Population Living in Miami-Dade County, Florida

Abstract: Florida has the greatest proportion (19%) of older population (65 years or older) in the United States. The age distribution of its residents, in conjunction with a major shift in the leading cause of death within all age groups from acute illnesses to chronic disease, creates unprecedented health care challenges for the state. The objective of this study is to profile the older population living in Miami-Dade County (MDC) using 3 population-based, household-based surveys conducted over the past 5 years.This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The older adult population in Miami-Dade County is majority Hispanic. The Hispanic population in the United States performs less physical activity than the non-Hispanic white population, and the Hispanic population in Miami-Dade County has a disproportionately greater burden of cardiovascular disease and high blood pressure than the non-Hispanic white population (8,9). Our study showed that Hispanic participants had significantly greater improvements in blood pressure and pulse than non-Hispanic white and non-Hispanic black participants after the 21-week program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The older adult population in Miami-Dade County is majority Hispanic. The Hispanic population in the United States performs less physical activity than the non-Hispanic white population, and the Hispanic population in Miami-Dade County has a disproportionately greater burden of cardiovascular disease and high blood pressure than the non-Hispanic white population (8,9). Our study showed that Hispanic participants had significantly greater improvements in blood pressure and pulse than non-Hispanic white and non-Hispanic black participants after the 21-week program.…”
Section: Discussionmentioning
confidence: 99%
“…Racial/ethnic minority populations have a disproportionate burden of multiple chronic conditions (4). Older adults, racial/ethnic minorities, and low income populations are more likely to be sedentary or more likely to not follow recommended physical activity guidelines than the general population (7,8). For example, non-Hispanic white adults aged 65 or older in the United States report higher levels of physical activity than same-aged non-Hispanic black and Hispanic adults (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…South Florida has a unique patient population with diverse ethnic and racial backgrounds, highest proportion of older adults as compared with other states, and with women outnumbering men at older ages. 1 A probability-sampled, householdbased survey in Miami-Dade County found that non-Hispanic whites constitute only 9.4% of the population with the majority being blacks, Hispanic, or Haitian blacks (non-English speaking ≈37.8%). 1 In this population, 53% of the residents had high school equivalent (or less) degree as formal education, and 34.5% were below the US poverty threshold.…”
Section: Local Challenges In Implementationmentioning
confidence: 99%
“…1 A probability-sampled, householdbased survey in Miami-Dade County found that non-Hispanic whites constitute only 9.4% of the population with the majority being blacks, Hispanic, or Haitian blacks (non-English speaking ≈37.8%). 1 In this population, 53% of the residents had high school equivalent (or less) degree as formal education, and 34.5% were below the US poverty threshold. 1 Furthermore, one quarter of all households had at least 1 member who was uninsured at some point, and 3 of 5 households had at least 1 member who used Medicare for coverage.…”
Section: Local Challenges In Implementationmentioning
confidence: 99%